COVID-19 Outbreak: Pathogenesis, Current Therapies, and Potentials for Future Management - Hossain, Md. Farhad; Hasana, Sharifa; Mamun, Abdullah Al; Uddin, Md. Sahab; Wahed, Mir Imam Ibne; Sarker, Sabarni; Behl, Tapan; Ullah, Irfan; Begum, Yesmin; Bulbul, Israt Jahan; Amran, Md. Shah; Rahman, Md. Habibur; et al. (Frontiers in Pharmacology, 2020)
At the end of 2019, a novel coronavirus (CoV) was found at the seafood market of Hubei province in Wuhan, China, and this virus was officially named coronavirus diseases 2019 (COVID-19) by World Health Organization (WHO). COVID-19 is mainly characterized by severe acute respiratory syndrome coronavirus-2 (SARS-CoV2) and creates public health concerns as well as significant threats to the economy around the world. Unfortunately, the pathogenesis of COVID-19 is unclear and there is no effective treatment of this newly life-threatening and devastating virus. Therefore, it is crucial to search for alternative methods that alleviate or inhibit the spread of COVID-19. In this review, we try to find out the etiology, epidemiology, symptoms as well as transmissions of this novel virus. We also summarize therapeutic interventions and suggest antiviral treatments, immune-enhancing candidates, general supplements, and CoV specific treatments that control replication and reproduction of SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV).